Regulation of the tumor suppressor PML by sequential post-translational modifications - Schmitz, Lienhard; Grishina, Inna (Frontiers in Oncology, 2012)
Posttranslational modifications (PTMs) regulate multiple biological functions of the PML (promyelocytic leukemia) protein and also the fission, disassembly and rebuilding of PML nuclear bodies (PML-NBs) during the cell cycle. Pathway-specific PML modification patterns ensure proper signal output from PML-NBs that suit the specific functional requirements. Here we comprehensively review the signaling pathways and enzymes that modify PML and also the oncogenic PML-RARα fusion protein. Many PTMs occur in a hierarchical and timely organized fashion. Phosphorylation or acetylation constitute typical starting points for many PML modifying events, while degradative ubiquitination is an irreversible end point of the modification cascade. As this hierarchical organization of PTMs frequently turns phosphorylation events as primordial events, kinases or phosphatases regulating PML phosphorylation may be interesting drug targets to manipulate the downstream modifications and thus the stability and function of PML or PML-RARα.